STEM-Integrated Problem-Based Learning in Green Chemistry to Enhance Chemical Literacy and Scientific Attitudes - Nelson Tairas; Eli Rohaeti; Anti Kolonial Prodjosantoso; Jaslin Ikhsan; Dyah Puspitasari Ningthias (Postgraduate, University of Mataram, 2025)
Students' low chemical literacy and scientific attitudes in understanding chemical concepts, particularly in green chemistry, pose significant challenges in chemistry education today. Traditional learning models are often less effective in fostering 21st-century skills, such as critical thinking and problem-solving, which are essential for a more relevant and applicable chemistry education. This study aims to evaluate the impact of a STEM integrated with Problem-Based Learning (PBL) model on students' chemical literacy and scientific attitudes in green chemistry. Employing a quasi-experimental design, the study involved two experimental classes and two control classes. Each group participated in pretests and posttests to assess their chemical literacy and scientific attitudes. The analysis revealed that the PBL-STEM model significantly enhanced students' chemical literacy (N-Gain = 0.54) and scientific attitudes (N-Gain = 0.46) compared to traditional learning methods. Although the improvement in scientific attitudes was more pronounced, the increase in chemical literacy was relatively lower, indicating the necessity for adjustments in instructional approaches to deepen students' understanding of chemical concepts. The integration of green chemistry principles within the PBL-STEM model effectively connected chemistry education with global environmental challenges while also fostering 21st-century skills such as critical thinking and problem-solving. This study concludes that the PBL-STEM model presents a promising alternative for enhancing the quality of chemistry education and preparing students to navigate the complexities of an ever-evolving world.